2017
DOI: 10.25179/tjem.2017-56543
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Nesfatin-1 Levels in Patients with Impaired Glucose Tolerance

Abstract: 65I In nc cr re ea as se ed d S Se er ru um m N Ne es sf fa at ti in n--1 1 L Le ev ve el ls s i in n P Pa at ti ie en nt ts s w wi it th h I Im mp pa ai ir re ed d G Gl lu uc co os se e T To ol le er ra an nc ce e B Bo oz zu ul lm mu uş ş G Gl lu uk ko oz z T To ol le er ra an ns sı ı O Ol la an nl la ar rd da a A Ar rt tm mı ış ş S Se er ru um m N Ne es sf fa at ti in n--1 1 D Dü üz ze ey yl le er ri i Purpose: Nesfatin-1 is a recently discovered energy-regulating peptide, widely expressed in both central an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
4
1
Order By: Relevance
“…In the present study, serum nesfatin-1 levels were lower in individuals diagnosed with metabolic syndrome. This result is similar to other studies investigating the metabolic syndrome and its components 21–24 26 27. In the present study, no significant difference was found between the BMI and body fat percentage of the case and control groups.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, serum nesfatin-1 levels were lower in individuals diagnosed with metabolic syndrome. This result is similar to other studies investigating the metabolic syndrome and its components 21–24 26 27. In the present study, no significant difference was found between the BMI and body fat percentage of the case and control groups.…”
Section: Discussionsupporting
confidence: 92%
“…This result is similar to other studies investigating the metabolic syndrome and its components. 21–24 26 27 In the present study, no significant difference was found between the BMI and body fat percentage of the case and control groups. In this case, the decrease in the level of nesfatin-1 indicates that there is no weight or body fat percentage.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…A modulation glucose metabolsm by peripheral rather than central nesfatin-1 . In a study by Akın et al (Akın et al, 2017), fasting plasma nesfatin-1 levels of patients with IGT were higher than the control group. The mean fasting nesfatin-1 levels of patients with IGT and control group were 2.1 ± 2.6 ng/mL, 0.5 ± 0.2 ng/mL, respectively (p=0.033).…”
Section: Nesfatin-1 and Glucose Homeostasismentioning
confidence: 87%